Sobre a possibilidade do conhecimento de si na dedução transcendental e nas reflexões sobre O Sentido Interno de Leningrado - Câmara, Pedro Pinheiro (2017)
This research discusses arguments about self-knowledge in the work Transcendental Deduction of the Critique of Pure Reason using as a strategy of analysis and study of the work the comparison of it with a Kantian manuscript found and published only at the end of the 20th century. It also uses, in order to deepen the theses, the commentators who notably held discussions on the subject. The research defends the importance of inner sense to understand the main argument and to characterize its specificities. Inner sense is a secondary theme, but very attached to the main problem. Time, which is the form of this inner sense, has been studied as the appearance of the subject in the sensibility and, therefore, crucial factor in the understanding of the Kantian subjectivity. This research was structured around some important distinctions to understand the theme under analysis, they are: between internal sense and external sense, and apperception and inner sense. Throughout the production of the arguments the systemic character of the Kantian thought was emphasized, which implies in a greater complexity in the definition of its elements since they are defined in relation to the others. The research concludes the specificity of the self-knowledge that is distinct from the knowledge in a strict sense, because it does not contain the qualifiers of a properly objective knowledge. From the conclusions also emerged the importance of the embodiment of the empirical subject as a way of apprehending oneself, expressing the relation between internal and external sense; as well as the self-affection as an important concept to understand the distinction of the inner sense from the transcendental apperception.